Analisis Perbandingan Kinerja Keuangan Sebelum Dan Sesudah Merger Dengan Menggunakan Metode Economic Value Added (Eva) Dan Market Value Added (Mva) Pada Pt Unilever Indonesia Tbk - Zulvina, Rakhmi Ayu; Musdholifah, Musdholifah (AKRUAL: JURNAL AKUNTANSI, 2010)
AbstractMerger is a decision to combine or merge two or more companies into one new company. One of the merged company in Indonesia is PT Unilever Indonesia Tbk with PT Knorr Indonesia in 2004. To identify and analyze it, EVA and MVA method is used, then the results of the calculations tested using normality test statistical tool kolmogorov smirnov, and carried out by means of differential test paired samples T-test.The increase ofÂ  EVA before and after the merger worth 125.30%. While the increase in MVA before and after the merger worth 227.33%. Increasing the value of MVA was more due to the companys market value, which is reflected in the share price and listed share, although not free from invested capital in the company